Analysis of Copyright Infringement of Cover Song Displayed on YouTube (Case Study of Supreme Court Decision Number 41 PK/PDT.SUS-HKI/2021) - Helga Paramesti Putri; Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2025)
In the era of globalization and digitalization, communication technology plays an important role in accelerating the development of digital activities. YouTube has become one of the popular platforms for sharing content, including song cover videos made by individuals or groups. Although it offers convenience and a means of creativity, song cover activities on YouTube have the potential to cause copyright infringement, especially related to musical works protected by law. Many users are unaware that uploading song covers without permission can violate copyright, which risks harming the creator and the music industry. This study aims to analyze copyright infringement in song cover activities on YouTube, focusing on a case study of the Supreme Court Decision Number 41 PK/Pdt.Sus-HKI/2021. The method used is normative legal research with a case study approach, which aims to provide an understanding of copyright protection in the digital world. The results of the study show that the Supreme Court's decision regarding copyright infringement in the case of